2022
DOI: 10.3390/math10203829
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Investment Awareness: A Moderating Structural Equation Modeling-Based Model in the Saudi Arabian Context

Abstract: In line with today’s economy, investment and financial awareness are necessary for success and an individual’s well-being, specifically for the younger generations. Therefore, this study aims to examine the relationships between financial literacy, saving behavior, a lack of self-control, family financial socialization, and investment awareness. Further, it investigates the moderating role of both family financial socialization and the lack of self-control in these relationships. Employing a quantitative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…When a family member, such as parents, has investment information and shares it with other family members, this motivates nonparticipant relatives to join in the investments [42]. Social impact may be one of the actions that shape saving behaviors as a result of investment awareness [12]. In the context of Saudi Arabia, the 2030 Saudi Vision has promoted investment awareness among Saudi people through the Capital Market Authority (CMA).…”
Section: Investment Awareness and Social Influencementioning
confidence: 99%
See 4 more Smart Citations
“…When a family member, such as parents, has investment information and shares it with other family members, this motivates nonparticipant relatives to join in the investments [42]. Social impact may be one of the actions that shape saving behaviors as a result of investment awareness [12]. In the context of Saudi Arabia, the 2030 Saudi Vision has promoted investment awareness among Saudi people through the Capital Market Authority (CMA).…”
Section: Investment Awareness and Social Influencementioning
confidence: 99%
“…Moreover, it helps students become aware of career alternatives and choices. Policymakers in Saudi Arabia have realized the importance of education support at the university level and its impact on student intention; therefore, they have added some investment courses to the existing curricula [12]. Keat et al [60] and Aliedan et al [61] confirmed that university education support positively impacts the entrepreneurial intentions of higher education students.…”
Section: Unversity Education Support and Risky Investment Intentionmentioning
confidence: 99%
See 3 more Smart Citations